TARIQ RAMADAN’S IDEA OF REFORM:: Realizing Integration of Knowledge (IoK) and Development of Islamic Economics (IE) - Jasmin Omercic, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
The necessity for reforms in the Muslim world is vivid and indubitable to many Muslim and non-Muslim scholars and has been addressed countless times. Reasons for reforms are just as apparent in contemporary times as a century ago or even earlier. Muslims have often been prevented from or have failed in and resisted reforms due to occupational-colonial, general socio-political, economic, traditional or taqlīd (blind belief/following) circumstances. Distinct responses and solutions to such states of Muslim and general human affairs have been the concern of Tariq Ramadan. His idea of reform reveals ignorance as the root cause of such state of affairs. It is therefore the task of this essay to explore the idea of Ramadan’s reform.